ANALYSIS OF THE USE OF CELLULAR OPERATORS USING THE ANALYTIC HIERARCHY PROCESS METHOD - Ari Muzakir; Usman Ependi (Journal of Information System and Informatics, 2019)
The development of technology in the telecommunications sector is now easier to be enjoyed by the community. Almost all regions have been able to enjoy the ease of access to information through telecommunications networks. Telecommunications service providers certainly have competed in such a way as to be able to hold users to remain loyal to the provider used. From several surveys conducted, there are still many users who cannot be loyal to use the services of these providers. The increasing number of communication network providers makes users more choices. Various ways are carried out by communication network providers to maintain their users such as giving bonuses, providing cheap rates, increasing services to the regions. In this study will focus on the level of customer satisfaction with cellular operators with a variety of criteria that have been prepared which will be a consideration for users in using these cellular operators. This research will use the AHP method (Analytic Hierarchy Process) to find out which cellular operators are the most superior based on the judgment of the user with various criteria each. So that in the end it will be known which cellular operators will be selected and purchased by consumers according to their respective needs. The results of this study show that based on the bonus, IM3 is the best with a weight of 0.21712. Then based on the price rate, a tri card with a weight of 0.16565. Furthermore, the service criteria show a better Sympathy card with a weight of 0.21311